The heart and the oesophagus: intimate relations. Issue 958 (5th August 2005) - Heatley, M; Rose, K; Weston, C
Abstract : The close anatomical relations of the heart and oesophagus, and the similarity of symptoms attributable to disorders of either organ, often lead to diagnostic difficulty in patients with chest pain. A definitive diagnosis of non-cardiac chest pain attributable to oesophageal reflux or spasm is hampered, both by the need for prolonged ambulatory monitoring of pH, manometry, and endoscopy, and by the common occurrence of asymptomatic reflux and spasm, and the corresponding difficulty in linking an episode of reflux or spasm with an episode of pain. Moreover, some patients with non-cardiac chest pain and normal tests of oesophageal structure and function have centrally mediated hypersensitivity, both within and without the oesophagus. Rather than proceed with investigations, in the absence of symptoms to suggest structural disease of the oesophagus, it would be reasonable to attempt symptomatic treatment with a proton pump inhibitor or an antidepressant.